2014
DOI: 10.1097/01.tp.0000441874.43007.81
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Islamic Religiosity and Attitude Toward Deceased Organ Donation Among American Muslims

Abstract: Higher levels of intrinsic religiosity or adherence to Islamic ethics do not appear to associate with negative attitudes toward deceased organ donation. Negative religious coping appears, however, to be related to lower rates of believing deceased organ donation to be justified. Future studies with larger samples that incorporate additional measures of religiosity can further clarify relationships between religiosity and organ donation attitude among Muslim communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
0
31
0
Order By: Relevance
“…widely studied, regional context and corresponding regulations/policies of organ donation vary among Islamic countries. On the other hand, while religion is indented as a barrier toward organ [23,24], there is evidence of encouraging the role of these beliefs [25], and this paradox is considerable among Muslims [26,27]. It is evident that control beliefs could be an important predictor of intention to be a donor [28,29].…”
Section: Although Religious Beliefs Especially Islamic Thought and Rmentioning
confidence: 99%
“…widely studied, regional context and corresponding regulations/policies of organ donation vary among Islamic countries. On the other hand, while religion is indented as a barrier toward organ [23,24], there is evidence of encouraging the role of these beliefs [25], and this paradox is considerable among Muslims [26,27]. It is evident that control beliefs could be an important predictor of intention to be a donor [28,29].…”
Section: Although Religious Beliefs Especially Islamic Thought and Rmentioning
confidence: 99%
“…Adherence to Islam is frequently cited as having a negative correlation with organ donation and transplant. In a study carried out in the USA, it was suggested that believing that hardships are a punishment from God was associated with negative attitudes toward donation . In one study, the relevance of religion was the same for the youth and the older generation ; however, another study found that the minority of Muslims with more positive attitudes were generally younger, more willing to learn about organ donation, and seemed to be more emotionally affected by the subject .…”
Section: Resultsmentioning
confidence: 99%
“…However, the proportion of individuals who had verified organ donor designation is somewhat lower than the proportion who self-reported donor designation in a national survey (Appendix Table 2) (14). Moreover, previous studies have been inconsistent on the effect of employment status, insurance, income, and comorbid conditions on willingness to donate (2,10,11,15). By contrast, we found that all four variables were strongly associated with verified donation designation.…”
Section: Discussionmentioning
confidence: 99%